HUBUNGAN ANTARA LAMA MENJALANI HEMODIALISIS DENGAN MEKANISME KOPING PASIEN PENYAKIT GINJAL KRONIK DI RUMAH SAKIT GATOEL MOJOKERTO - FitriaWahyu Ariyanti; Henry Sudiyanto (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2017)
Patients with chronic 5-stage kidney disease require long-term or lifelong hemodialysis therapy that causes stress and requires coping in response. The purpose of this study was to analyze the correlation between long undergoing hemodialysis with coping mechanisms of patients with chronic kidney disease at Gatoel Hospital of Mojokerto. This type of research was correlational. The population of patients undergoing Hemodialisa at Gatoel Mojokerto Hospital was 179 with a sample of 123 people. The sampling technique used was Proportionate Random Sampling. Data collection using questionnaire. Data analysis using Chi-square test (X2). The results showed that almost all respondents had undergone hemodialysis >1 years as many as 88 people (71,5%) and most of respondent had maladaptive coping mechanisms as many as 71 people (57,7%). The result of statistical test by using Chi Square test showed signification level 0.000 <α (0.05), it means there was relatioship between long undergoing hemodialysis with coping mechanisms of patients with chronic kidney disease at Gatoel Hospital of Mojokerto. Based on the results of the study can be concluded that patients who have long undergone hemodialysis already in the acceptance phase while newly diagnosed patients should undergo hemodialysis often feel afraid, worried about the condition of the illness.